Generative artificial intelligence in academic writing in higher education: A systematic review - Chanpradit, Thaweesak (Edelweiss Applied Science and Technology, 2025)
The growing integration of generative artificial intelligence tools in higher education has not met with comprehensive guidelines regarding the use of GenAI in academic writing, especially in English language teaching and learning. This review seeks to fill this gap by identifying and synthesizing research that examines the roles, benefits, challenges, and ethical considerations of GenAI published between 2023 and 2024. The PRISMA procedure was used to identify research articles that resulted in 30 studies selected for the review. The findings of the review identified the significant role that generative AI plays in enhancing the cohesion, precision, clarity, and engagement of academic writing, offering improved creativity, fluency, and proficiency. However, it also identified challenges, including the risks of plagiarism, over-reliance on AI tools and their generated text, diminished creativity, ethical misconduct, and limitations in interpreting nuanced information and producing authentic content. Issues such as hallucinations, biases, cultural insensitivity, unequal access to AI technologies, and inadequate AI literacy further complicate the integration of GenAI. Ethical considerations, particularly institutional guidelines and transparent data management, are critical to ensuring the responsible use of AI. Human oversight and institutional support, including structured training and equitable access, are also necessary to address these challenges.